The Effect of Return on Assets, Debt to Equity, and Total Asset Turnover on Earnings Growth with Company Size as a Moderating Variable in Basic Industry and Chemical Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 Period - Devi, Devi; Tandiah, Ester; Salim, Maria (Journal of Applied Business Administration, 2025)
This study aims to test and analyze the effect of return on assets, debt to equity, and total asset turnover on earnings growth with company size as a moderating variable in manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The study population was 170 companies. The method used in sampling based on criteria (purposive sampling) obtained 49 companies as samples with a total of 196 observations. The secondary data collection method includes annual financial reports, journals, and related books. This research is quantitative, data analysis is done through PLS-SEM with a two-stage test approach using the Smart PLS 3.0 program. The results showed that return on assets and debt to equity partially had a significant positive effect on earnings growth while total asset turnover partially did not affect earnings growth. Company size is unable to moderate return on assets, debt to equity, and total asset turnover on earnings growth. The implication of this research is to provide insight for company management to pay more attention to the efficiency of asset use and capital structure management to increase profit growth, as well as provide information for investors in considering financial factors before making investment decisions in basic and chemical industry sector companies.